Bedingungen des transalpinen Eisenbahnverkehrs. Bericht von der Jahrestagung der FER. - Uhlenhut, Bernd H. (Deutscher Verkehrs-Verl., 2007)
Am 28. März 2007 fand in Luzern die diesjährige Jahrestagung der Forschungsstelle für deutsches und internationales Eisenbahnrecht (FER) statt. Nach einem einleitenden Beitrag zum europarechtlichen Rahmen stellten die Beiträge die Zugangsregulierung in Deutschland, Österreich, der Schweiz und schließlich Italien dar. difu

On 28 March 2007, the annual meeting of the "Forschungsstelle für deutsches und internationales Eisenbahnrecht" was held in Lucerne (Switzerland). The introductory speech covered aspects of European law while subsequent contributions dealt with access regulations in Germany, Austria, Switzerland and Italy. This helped to facilitate comparisons to be made of the various regulations in place and of their application. The meeting also offered an overview of the organizational arrangements in place for trans-border transport, which carriers take into consideration in case of technical and legal difficulties. difu
Keywords: Öffentlicher Verkehr; Eisenbahn; Schienenverkehr; Verkehrsinfrastruktur; Europarecht; Eisenbahnrecht; Tagungsbericht; Infrastrukturzugang; Bundesnetzagentur; Regulierungsbehörde